THE IMPACT OF SELF-ESTEEM ON THE DEGREE OF GENERAL AND EXAMINATION ANXIETY - Georgievska, Sofija (Ревија за социјална политика/Journal of Social Policy, 2015)
The purpose of this research was to clarify the relationship to the level of self esteem and general and examination anxiety, as well as to determine the difference between general and examination anxiety among the students. Measuring instruments that were used in this research are Rosenberg self-esteem Scale, anxiety scale constructed by Hamilton and Test Anxiety Inventory (TAI).